Executive EQ : emotional intelligence in business - Cooper, Robert (London, United Kingdom : Orion Business, 1997)
There's more to success than having a high IQ. Knowing when to trust a colleague, when someone is on the verge of a nervous breakdown, or when to laugh at the boss's jokes are every bit as vital to workplace survival as understanding the latest regulatory policies or interpreting the company's balance sheet.
The first cornerstone : emotional literacy -- The second cornerstone : emotional fitness -- The third cornerstone : emotional depth -- The fourth cornerstone : emotional alchemy
Keywords: PSYCHOLOGY, INDUSTRIAL